Platinum-free, graphene based anodes and air cathodes for single chamber microbial fuel cells. Issue 45 (9th November 2017) - Call, Toby P.; Carey, Tian; Bombelli, Paolo; Lea-Smith, David J.; Hooper, Philippa; Howe, Christopher J.; Torrisi, Felice
Abstract : In this work graphene-based aerogel anodes and graphene/stainless steel cathodes have been optimised as platinum-free electrodes in Rhodopseudomonas palustris microbial fuel cells, achieving a maximum power output of ∼3.5 W m −3 . Abstract : Microbial fuel cells (MFCs) exploit the ability of microorganisms to generate electrical power during metabolism of substrates. However, the low efficiency of extracellular electron transfer from cells to the anode and the use of expensive rare metals as catalysts, such as platinum, limit their application and scalability. In this study we investigate the use of pristine graphene based electrodes at both the anode and the cathode of a MFC for efficient electrical energy production from the metabolically versatile bacterium Rhodopseudomonas palustris CGA009. We achieve a volumetric peak power output ( P V ) of up to 3.51 ± 0.50 W m −3 using graphene based aerogel anodes with a surface area of 8.2 m 2 g −1 . We demonstrate that enhanced MFC output arises from the interplay of the improved surface area, enhanced conductivity, and catalytic surface groups of the graphene based electrode. In addition, we show a 500-fold increase in P V to 1.3 ± 0.23 W m −3 when using a graphene coated stainless steel (SS) air cathode, compared to an uncoated SS cathode, demonstrating the feasibility of a platinum-free, graphene catalysed MFCs. Finally, we show a direct application for microwatt-consuming electronics by connecting several of these coin sized devices in series to power a digital clock.